PERSEPSI PENGGUNA TERHADAP PENERAPAN AI UNTUK ANALISIS KOMENTAR MEDIA SOSIAL - Amanda Putri Rizkita; Nadine Octavianta; Habibah Zahra Siregar; Salsabilla Khairus Syifa; Dila Handayani (Jurnal Komputer dan Teknologi, 2026)
This study examined user views on the use of artificial intelligence (AI) to analyze comments on Indonesian-language social media. Of the 50 respondents, 92% said AI was useful for understanding public opinion, while 8% still doubted the accuracy of the analysis results. While 88% felt AI could speed up the process of recognizing sentiment in comments, 74% felt the technology did not fully understand Indonesian casual language and social context. Furthermore, 81% agreed that the use of AI should be ethically supervised to prevent errors in data interpretation and use. The results showed that users generally held a positive and optimistic view of the future of AI, although adjustments were still needed regarding language and user ethics in Indonesia's digital world.